Improving students’ creative writing skill in composing interpersonal text through comic strips in distance learning - Lailatul Abidah (Jurnal Pendidikan Profesi Guru, 2023)
Writing is one of the skills that high school students should master. However, the difficulty of mastery of writing skills makes students' scores tend to be low and does not reach the minimum standard of mastery (KKM). In addition, this makes students less motivated in participating learning activities, one of which is in making interpersonal texts. The objectives of this research are: 1) to improve twelfth grade students’ creative writing skill, especially in making interpersonal texts through comic strips; and 2) increase students’ motivation in learning English in distance learning class of the twelfth grades students of Senior Vocational School (SVS) 1 of Bunga Raya in the academic year of 2020/2021. This classroom action research (CAR) was conducted in two cycles by which each cycle consisted of planning, acting, observing and reflection. The result shows that there is an improvement of students’ creative writing skill. It can be seen from the result of students’ average score in doing the posttest in cycle II was above KKM value. Besides, the improvement of the group project assessment showed a very significant results.